(untitled) (DAPesquisa, 2021)
This article discusses the theme of the construction of stereotyped social representation of the sertão and sertanejo from the exploration of the image of the cangaço. Using Serge Moscovici’s theory of social representations and Duval Albuquerque’s analysis of the invention of the Northeast, we analyzed the forms and themes from which the illustrated press and even the cinema of the 1950s explored the representation of cangaço for print the image of savagery to the sertão, making the hinterland culture and its true social tensions invisible, reducing the sertão to a stereotyped character.